Metacognitive effects of attitudinal (in)congruence on social media: relating processing fluency, subjective knowledge, and political participation - Frauhammer, Luna T.; Neubaum, German (Frontiers in Psychology, 2023)
Introduction Encountering political disagreements in our daily lives can discourage us from participating in democratic processes. To date, research has mainly focused on social motives or attitudinal mechanisms to explain this phenomenon. In the present study, we adopt a different approach and highlight metacognitive effects of attitudinal (in)congruence on processing fluency (i.e., perceived ease of processing) and subjective knowledge as well as their relationship with behavioral outcomes such as the intention to politically participate. Methods In a pre-registered online experiment (N = 1,258), participants saw a political social media post with six opinionated user-generated comments. These comments either all matched (congruent condition) or contradicted (incongruent condition) participants’ personal opinions. Processing fluency, issue specific subjective knowledge, and intention to politically participate were then measured using established self-report scales. Results In line with our hypotheses, the congruent stimuli evoked a higher feeling of processing fluency than the incongruent ones (d = 0.21). Furthermore, participants in the congruent condition indicated a higher intention to politically participate (d = 0.23) and rated their own knowledge on the topic as higher (d = 0.22) than participants in the incongruent condition—even though the factual knowledge gain should be equal in both conditions. Finally, we observed positive relationships between processing fluency and subjective issue knowledge ( = 0.11) as well as between subjective issue knowledge and issue-specific political participation ( = 0.43). Discussion Our findings highlight the importance of considering metacognitive constructs such as subjective knowledge to explain political behaviors and suggest that attitudinal congruence influences the way we perceive our own knowledge and information processing.